Hubungan pola asuh orangtua dengan tingkat kecemasan anak usia 6-12 tahun pada tindakan pencabutan gigi - Zakiah Balqis, Izza; Sulistyani, Herastuti; Yuniarly, Etty (Poltekkes Kemenkes Yogyakarta, 2019)
The anxiety in children when visiting a dentist results in children not wanting to check the condition of their oral cavity to the dentist, therefore it causes many problems with their oral and dental health. Children who visit a dentist experience an anxiety level of 5% to 52%. The behavioral problem in the children with excessive anxiety tends to have multifactorial, one of which is the parenting. This research to investigate the correlation between parenting and the anxiety levels of children aged 6-12 years in the tooth extraction. This research was analytical survey research using a cross sectional design. The subjects of this research were children patients and their parents, who visit Private Dental Clinics for tooth extraction, as many as 47 respondents. Sampling used the accidental sampling technique. The research instrument used questionnaires to see their parenting, and also used the Facial Image Scale to see the level of anxiety. The parenting method showed the democratic parenting as much as 40.4%. The children’s anxiety level showed the anxiety level of anxious as much as 55.3%. The analysis results of the Lambda test analysis showed the democratic parenting with the level of child anxiety was 0.07, permissive parenting with the level of child anxiety was 0.008 and authoritarian parenting with the level of child anxiety was 0.007. Parents with democratic parenting is not related to children's anxiety level, authoritarian and permissive parenting are related to children's anxiety level.